ATRAKSI, AMENITAS DAN AKSESIBILITAS DALAM PENGEMBANGAN DESTINASI WISATA DI KECAMATAN WATUMALANG KABUPATEN WONOSOBO - Farida Nur Aini; Taufik Purboyo (Fakultas Ilmu Sosial Dan Politik, Universitas Wijayakusuma Purwokerto, 2022)
Tourism is a commodity that is able to move the wheels of the economy of a region so it needs to be developed properly. This study aims to determine and describe the elements of attractions, amenities and accessibility of tourist areas in Watumalang District, Wonosobo Regency. These factors are factors that determine success in the development of tourist destinations. The development of tourism product components such as attractions, amenities and accessibility allows managers to increase the number of visits and tourist satisfaction. This study uses a descriptive qualitative research method which means the researcher only explains the facts and knowledge found during the research through words or tables. Based on the data obtained in the study, the researcher found that (1) tourist attractions were sufficient and this was evidenced by the existence of several superior locations in the area; (2) amenities in the form of public facilities and supporting facilities still need to be improved to make it more satisfying for tourists; (3) accessibility has been fulfilled enough even though the facts show that there is still a lack of accessibility for people from outside the Wonosobo Regency area so that the number of tourists from outside the Regency is still below the number of tourists from within the Regency. Keywords: tourism, development, attractions, amenities, accessibility.